EFEK LAMA PERENDAMAN EKSTRAK KALAMANSI (Citrus microcarpa) TERHADAP AKTIVITAS ANTIOKSIDAN TEPUNG PISANG GOROHO (Musa spp.) - Kiay, Nancy; Suryanto, Edi; Mamahit, Lexie (CHEMISTRY PROGRESS, 2011)
ABSTRACTKiay et al., 2011. The effect calamansi (Citrus microcarpa) extract on antioxidant activity of goroho banana fluor(Musa spp.).Banana is local food commodity that used as sources of carbohydrate beside paddy. Fresh mature banana canbe produced as banana flour to prolong its lifetime and minimalize its nutrition degradation. Callamansi (Citrusmicrocarpa) contained antioxidant compound. Does callamansi extract improve antioxidant activity of gorohobanana flour. The aim of this research was to determine antioxidant activity of goroho banana flour whichimmersed with calamansi extract.This research using laboratory experiment methods to analyze total phenolic content, free radical scavengingactivity, total antioxidant and vitamins C of calamansi and goroho banana flour using spectrophotometer UV-vis.This research using complete random design (rancangan acak lengkap, RAL), thus obtained data wereanalyzed using statistic. Significant difference between groups were analyzed using ANOVA with p<0,05. Ifthere is significant difference between groups, data were analyzed using Duncan’s multiple range test (DMRT).The results showed that banana flour immersed with calamansi extract possess to total phenolic content 3,84mg/kg gallic acid, free radical scavenging activity 81,20%, total antioxidant 28,42 ppm and vitamins C 0,09mg/100 g sample (p>0,05) compared with vitamin C, citric acid and blank. Its caused by callamansi antioxidantdiffuse into banana flour. Banana flour immersed with vitamins C possess to total phenolic content 1,66 mg/kggallic acid, free radical scavenging activity 41,98%, total antioxidant 22,8 ppm and vitamins C 0,09 mg/100 gsample, Banana flour immersed with citric acid possess to total phenolic content 1,42 mg/kg gallic acid, freeradical scavenging activity 36,66%, total antioxidant 15,15 ppm and vitamins C 0,09 mg/100 g sample andblank possess to total phenolic content 1,49 mg/kg gallic acid, free radical scavenging activity 39,94%, totalantioxidant 16,63 ppm and vitamins C 0,09 mg/100 g sample. Antioxidant activity from calamansi extract andgoroho banana flour caused by it phenolics compound that act as antioxidant.As conclusions of this research, calamansi possess an antioxidant activity. Then goroho banana flour immersedwith calamansi extract possess high antioxidant activity. This research suggested that calamansi extract can beused to produce banana flour with antioxidant activity..Keywords : callamansi, goroho banana, flour, antioxidant